Factors Affecting Price, Volume and Credit Risk in the Consumer Finance Industry: Discussion - Goudzwaard, Maurice B. (Journal of Finance, 1970)
Maurice B. Goudzwaard, Factors Affecting Price, Volume and Credit Risk in the Consumer Finance Industry: Discussion, The Journal of Finance, Vol. 25, No. 2, Papers and Proceedings of the Twenty-Eighth Annual Meeting of the American Finance Association New York, N.Y. December, 28-30, 1969 (May, 1970), pp. 526-528